THE DIALECTIC OF MELANCHOLY: A MODEL FOR UNDERSTANDING THE PRODUCTION OF ADAPTED SUBJECTIVITIES - Silva, Mariana Bergo Damaso (Seven Editora, 2025)
Based on the problem of the impossibility of forming the individual in a social organization based on barbarism, the constitution of melancholy is analyzed, whose characteristic of maintaining the memory of the pain experienced questions survival in a state of inversion of means and ends, which mutilates the individual while summoning them to participate in a reality that is alien to their realization as such. Contrary to what is demanded by neoliberal culture, the melancholic state, while manifesting the impediments inflicted on the individual, indicates the possibility of resisting these conditions by renouncing the untruth of the imposed meaning and can also signal an ethical-political orientation of present action because its movement brings traces of non-forgetfulness, a fundamental condition for critical reflection on the contemporary imposition of the social process of adaptation.DOI: https://doi.org/10.56238/sevened2025.036-094